Differential Effects of Carbohydrates on Arabidopsis Pollen Germination. (10th February 2017) - Hirsche, Jrg; Garca Fernndez, Jos M.; Stabentheiner, Edith; Grokinsky, Dominik K.; Roitsch, Thomas
Abstract : Pollen germination as a crucial process in plant development strongly depends on the accessibility of carbon as energy source. Carbohydrates, however, function not only as a primary energy source, but also as important signaling components. In a comprehensive study, we analyzed various aspects of the impact of 32 different sugars on in vitro germination of Arabidopsis pollen comprising about 150 variations of individual sugars and combinations. Twenty-six structurally different mono-, di- and oligosaccharides, and sugar analogs were initially tested for their ability to support pollen germination. Whereas several di- and oligosaccharides supported pollen germination, hexoses such as glucose, fructose and mannose did not support and even considerably inhibited pollen germination when added to germination-supporting medium. Complementary experiments using glucose analogs with varying functional features, the hexokinase inhibitor mannoheptulose and the glucose-insensitive hexokinase-deficient Arabidopsis mutant gin2-1 suggested that mannose- and glucose-mediated inhibition of sucrose-supported pollen germination depends partially on hexokinase signaling. The results suggest that, in addition to their role as energy source, sugars act as signaling molecules differentially regulating the complex process of pollen germination depending on their structural properties. Thus, a sugar-dependent multilayer regulation of Arabidopsis pollen germination is supported, which makes this approach a valuable experimental system for future studies addressing sugar sensing and signaling.